Carbohydrate intake during prolonged cycling minimizes effect of glycemic index of preexercise meal - Burke, L. M.; Claassen, A.; Hawley, J. A.; Noakes, T. D. (Journal of Applied Physiology, 1998)
We studied the effects of the glycemic index (GI) of preexercise meals on metabolism and performance when carbohydrate (CHO) was ingested throughout exercise. Six well-trained cyclists performed three counterbalanced trials of 2-h cycling at approximately 70% of maximal oxygen uptake, followed by a performance ride of 300 kJ. Meals consumed 2 h before exercise consisted of 2 g CHO/kg body mass of either high-GI potato (HGI trial) or low-GI pasta (LGI trial), or of a low-energy jelly (Con trial). Immediately before and throughout exercise, subjects ingested a 10 g/100 ml [U-14C]glucose solution for a total of 24 ml/kg body mass. Despite differences in preexercise glucose, insulin, and free fatty acids concentrations among trials, both total CHO oxidation for HGI, LGI, and Con trials, respectively, during steady-state exercise [403 +/- 16, 376 +/- 29, and 373 +/- 24 (SE) g/2 h] and oxidation of the ingested CHO (65 +/- 6, 57 +/- 6, and 63 +/- 5 g/2 h) were similar. There was no difference in time to complete the subsequent performance ride (946 +/- 23, 954 +/- 35, and 970 +/- 26 s for HGI, LGI, and Con trials, respectively). When CHO is ingested during exercise in amounts presently recommended by sports nutrition guidelines, preexercise CHO intake has little effect on metabolism or on subsequent performance during prolonged cycling (approximately 2.5 h).